2019
DOI: 10.22630/aspe.2019.18.3.30
|View full text |Cite
|
Sign up to set email alerts
|

Professional Activity of Parents Receiving Family 500+ Child Support in Rural and Urban Areas

Abstract: The purpose of this study is to analyse the professional activity of parents who receive the Family 500+ educational benefit. Eligibility for this benefit in the first three years of the programme was dependent on family income and the number of children. Research shows that the highest level of professional activity was among parents who had one child and they did not receive a child benefit. Parents who received a 500+ benefit and had two or more children were more active in the labour market than pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It has been observed that beneficiaries happen to be reluctant to search for a job or to continue their employment, especially in case of the persons with low income (Blundell et al 2000;Haan, Myck, 2007) and among Polish mothers (Myck, 2016;Magda, Kiełczewska, Brandt, 2018). Parents who were granted the 500+ benefits who had at least two children are more professionally active than one child families (Kmieć 2019). In general, the authorities could be satisfied with the pro-family effects of the 500+ Programme.…”
Section: Family 500+ Programme Versus Polish Pro-family Policymentioning
confidence: 99%
“…It has been observed that beneficiaries happen to be reluctant to search for a job or to continue their employment, especially in case of the persons with low income (Blundell et al 2000;Haan, Myck, 2007) and among Polish mothers (Myck, 2016;Magda, Kiełczewska, Brandt, 2018). Parents who were granted the 500+ benefits who had at least two children are more professionally active than one child families (Kmieć 2019). In general, the authorities could be satisfied with the pro-family effects of the 500+ Programme.…”
Section: Family 500+ Programme Versus Polish Pro-family Policymentioning
confidence: 99%
“…Magda et al (2018) suggested that the labour market participation rates of women with children decreased after the introduction of the "Family 500+" programme compared to childless women. The influence of the "Family 500+" programme on the female labour market was studied also by Ruzik-Sierdzińska (2017), Radzik (2017) and Kmieć (2019). Some of the studies present evidence on the impact of the "Family 500+" programme to poverty and income inequality reduction.…”
Section: Introductionmentioning
confidence: 99%